Microstructural optimization through heat treatment for enhancing the fracture toughness and fatigue crack growth resistance of selective laser melted Ti–6Al–4V alloy - Kumar, Punit (2021)
The yield strength (σᵧ) of Ti–6Al–4V alloy, additively manufactured via selective laser melting (SLM) of powder beds, can exceed 1000 MPa while possessing a mode I fracture toughness (Kιc) of ∼50 MPa√m. The possibility of enhancing Kιc as well as fatigue crack growth resistance, without a significant penalty on σᵧ, via a judicious heat treatment process that transforms martensitic α’, which is present in the as-SLM microstructure due to rapid cooling of the molten metal, into an α/β phase mixture is examined. It was demonstrated that duplex annealing at temperatures below the β transus temperature of the alloy would lead to such a microstructure while retaining the mesostructure, whose nature depends on the process parameter combinations utilized. Near-doubling of the fracture toughness with only a ∼20% reduction in σᵧ was noted upon heat treatment. While the strength becomes isotropic after heat treatment, significant anisotropy in the fracture toughness of the heat-treated alloy with columnar prior β structure was noted. While the steady state fatigue crack growth (FCG) rates are comparable to corresponding values of the same alloy, but manufactured using conventional means, the threshold for fatigue crack initiation (ΔK₀) increases by 34%–56%. The enhancement in ΔK₀ was found to be a result of the transition in the near-threshold crack growth, from trans-to inter-granular and caused by the α/β basket weave microstructure, which imparts a high crack path tortuosity. Overall, this study demonstrates that post-processing heat-treatment can improve the damage tolerance of SLM Ti64 by increasing both Kιc and ΔK₀.